Oldřich Tůma a Tomáš Vilímek (eds.): Opozice a společnost po roce 1948. Česká společnost po roce 1945. [Opposition and Society after 1948. Czech Society after 1945], vol. 6.: Prague: Institute for Contemporary History, Academy of Sciences, Czech Republic v. v. i., 2009, 224 pp. - Soukupová, Blanka (Lidé města, 2011)
A review of the book by Oldřich Tůma and Tomáš Vilímek.